Intramolecular Hydrogen Bonding Restricts Gd–Aqua‐Ligand Dynamics. Issue 20 (11th April 2017) - Boros, Eszter; Srinivas, Raja; Kim, Hee‐Kyung; Raitsimring, Arnold M.; Astashkin, Andrei V.; Poluektov, Oleg G.; Niklas, Jens; Horning, Andrew D.; Tidor, Bruce; Caravan, Peter
Abstract: Aqua ligands can undergo rapid internal rotation about the M−O bond. For magnetic resonance contrast agents, this rotation results in diminished relaxivity. Herein, we show that an intramolecular hydrogen bond to the aqua ligand can reduce this internal rotation and increase relaxivity. Molecular modeling was used to design a series of four Gd complexes capable of forming an intramolecular H‐bond to the coordinated water ligand, and these complexes had anomalously high relaxivities compared to similar complexes lacking a H‐bond acceptor. Molecular dynamics simulations supported the formation of a stable intramolecular H‐bond, while alternative hypotheses that could explain the higher relaxivity were systematically ruled out. Intramolecular H‐bonding represents a useful strategy to limit internal water rotational motion and increase relaxivity of Gd complexes. Abstract : Stop the spin : For Gd 3+ complexes used in magnetic resonance imaging, rapid rotation of the aqua ligand about the Gd−O bond results in diminished relaxivity. Attenuation of this internal motion is demonstrated to result from the formation of an intramolecular hydrogen bond to the aqua ligand.